Studi Eksperimen Optimasi Sudut Pengapian Terhadap Daya Pada Motor Bakar 4 Langkah 1 Slinder Dan Rasio Kompresi 9,5:1 Dengan Variasi Campuran Bensin Premium Dan Bioetanol - Ahmad Nur Rokman; Romy Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Currently, the amount of fosil fuel in Indonesia is forecast limited, so that in the future will be likely fuel oil depletion that lead to increase the its price. Therefore, it is urgently to look for other alternative of fuel oil sources. Indonesia has a renewable alternative of fuel source that is bioethanol. The bioethanol can be blended with gasoline to improve the performance on gasoline. The purpose of this study is to determine the optimum angle for different concentrations of a mixture of ethanol and gasoline to produce optimal engine work. In this study, the effects of using unleaded gasoline (E0) and unleaded gasoline–ethanol blends (E10, E20,E30, E40 and E50) on engine performance. The investigation was conducted on a Suzuki Shogun 125 R single-cylinder, four-stroke, spark ignition engine. The experiments were performed by varying the ignition angle (150, 200 and 250) and speed of the crankshaft (2000 rpm, 3000 rpm and 4000 rpm). A result for the maximum effective braking power was on E20, the ignition angle of 20 degrees before TDC (Top Dead Center) at the crankshaft speed of 2000 rpm that was 156.284635 Watt, minimum SFC (Specific Fuel Consumption) was on E10, the ignition angle of 15 degrees before TDC, at the crankshaft speed of 2000 rpm that was 5.63 x 10 -7 kg / J. The thermal of maximum braking efficiency was on the E10, the ignition angle of 15 degrees before TDC at the crankshaft speed of 2000 rpm was 4.2%.Keywords: Internal Combustion Engine, Bioethanol, Ignition Angle